Psychological perspectives on divine forgiveness: seeking divine forgiveness - Fincham, Frank D.; Maranges, Heather M. (Frontiers in Psychology, 2024)
Seeking divine forgiveness (forgiveness by a Supreme Being or Higher Power) is important because the perception of such forgiveness is associated with psychological well-being This paper is the first to examine a process model of divine forgiveness in which the decision to pursue such forgiveness initiates the process of seeking it. (Fincham & May, 2023a). Two studies investigate the likelihood of seeking divine forgiveness. Study 1 (N = 190) introduces and provides discriminant validity for a unidimensional measure divine forgiveness seeking. Convergent validity is provided by demonstrating that seeking divine forgiveness correlates with reported experiences of divine forgiveness both concurrently and six weeks later. Study 2 (N = 390) provides a confirmatory factor analysis of seeking divine forgiveness scale items identified in Study 1 and replicates the concurrent and temporal association with reported experiences of divine forgiveness using a longer time interval (12 weeks). It also documents associations between a person’s image of God, attachment and closeness to God and the likelihood of seeking divine forgiveness. Both studies control for religiosity and Study 2 introduces an additional control for impression management. Together, they provide support for the idea that the decision to pursue divine forgiveness begins the process of seeking such forgiveness. We discuss limitations of the research and outline several paths for additional studies.